Preclinical efficacy and safety of an anti-human vegfa and anti-human nrp1 dual-targeting bispecific antibody (Idb0076) - Ko, Jong Hee; Kwon, Hyuk Sang; Kim, Bomin; Min, Gihong; Shin, Chorong; Yang, Seok Woo; Lee, Seong Wook; Lee, Youngmin; Hong, Dahae; Kim, Yong Sung (Biomolecules, 2020)
Although bevacizumab (Avastin®) has been approved as an antiangiogenic agent against some cancers, the efficacy is transient and unsatisfactory in other cancers most likely owing to the presence of alternative proangiogenic factors. Therefore, simultaneous blocking of several proangiogenic factors may be a promising strategy for antiangiogenic cancer therapeutics. Accordingly, neuropilin-1 (NRP1) is an attractive target because it serves as a multifunctional receptor for the vascular endothelial growth factor (VEGF) family. Here, we aimed to generate and test an anti-VEGFA and anti-NRP1 dual-targeting bispecific antibody (named as IDB0076) by genetic fusion of an NRP1-targeting peptide to the C-terminus of the bevacizumab heavy chain. Similar to the parental antibody (bevacizumab), IDB0076 suppressed VEGFA-induced migration of human endothelial cells. In contrast, IDB0076 inhibited endothelial-cell migration induced by other angiogenesis growth factors and manifested a more potent antitumor activity than that of bevacizumab in a murine tumor xenograft model. When toxicity was preliminarily evaluated in cynomolgus monkeys, IDB0076 showed no substantial adverse effects, e.g., the absence of noticeable nephrotoxicity, which has previously been documented for the combination therapy of bevacizumab and an anti-NRP1 antibody. Thus, VEGFA-and-NRP1 dual-targeting bispecific antibody IDB0076 may be a potent and safe anticancer agent worthy of further preclinical and clinical studies.
Keywords: Animals; Antibodies, Bispecific; Antineoplastic Agents; Cell Line; Cell Movement; Endothelial Cells; Humans; Macaca fascicularis; Male; Mice; Mice, Inbred BALB C; Mice, Nude; Neuropilin-1; Rats; Rats, Sprague-Dawley; Vascular Endothelial Growth Factor A; Angiogenesis; Bispecific antibody; IDB0076; Neuropilin-1; Vascular endothelial growth factor A